Usage of Mobile Laboratories of Biological Expertise Abroad and in Russia: Present Day Realities and Prospects - I. G. Karnaukhov; I. N. Sharova; E. S. Kazakova; K. M. Morozov; S. A. Shcherbakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2018)
We analyzed the data on availability and usage of mobile laboratories of biological expertise for indication and identification of pathogenic biological agents in foreign countries and in the Russian Federation. We outlined the major types of mobile units that exist abroad and in Russia. Key stages of evolution in design and deployment of mobile laboratories in the network of plague control institutions of the Rospotrebnadzor were described, as well as the broadening of the range of their use in Russia. We assessed operational use of the Russian mobile laboratories, both in Russia and abroad, in the provision of sanitary-epidemiological welfare during mass events, disaster management, and response to epidemic manifestations of particularly dangerous infectious diseases. Major trends in implementation of mobile units of biological expertise in Russia were identified. We addressed their usage in various State Programs on assistance to partner-countries in the matters of International Health Regulations (2005) implementation, control over dangerous infectious diseases. Advanced inventions – Second generation modernized mobile complex of the specialized anti-epidemic teams, mobile laboratory for monitoring and diagnostics, and airmobile anti-epidemic complex – were discussed.